Flap Reconstruction of the Abdominal Wall - Roubaud, Margaret S.; Baumann, Donald P. (Seminars in Plastic Surgery, 2018)
Due to the abundant and lax tissue of the abdominal wall, most ventral trunk defects are amenable to local soft tissue closure. However, when abdominal defects are accompanied by a lack of soft tissue, the surgeon faces a more complex subset of reconstructions. Three important principles guide the reconstruction of these wounds: timing of closure, careful assessment of the true extent of the wound, and the components of the defect. This article focuses on these three guiding principles and suggests the authors' preferred technique for these difficult defects.
Keywords: abdominal wall reconstruction; pedicled flap; free flap; hernia; surgical mesh; reconstructive surgical procedures; postoperative complications; component separation